По определению
поэтому 1) при 2) при х|x-1|-2x≥0 х|x-1|-2x<0 x|x-1|-2x=x²-2 x|x-1|-2x=-x²+2 x|x-1|=x²+2х-2 x|x-1|=-x²+2х+2 Раскрываем модуль при х≥1, т.е. х∈[1;+∞)|x-1|=x-1x(x-1)=x²+2х-2 x(x-1)=-x²+2х+2х²-х=х²+2х-2 х²-х =-х²+2х+2 -3х=-2 2х²-3х-2=0 х=2/3 ∉[1;+∞) D=(-3)² -4·2·(-2) =25 x=(3-5)/4=-0,5∉ [1;+∞) x=(3+5)/4=2∈ [1;+∞) x=2 - корень уравнения Раскрываем модуль при х<1, т.е. х∈(-∞;1)|x-1|=-x+1x(-x+1)=x²+2х-2 (*) x(-x+1)=-x²+2х+2 (**)-х²+х=х²+2х-2 -х²+х =-х²+2х+2 2х²+3х-2=0 -х=2D=3² -4·2·(-2) =25 х=-2∈(-∞;1)x=(-3-5)/4=-2∈(-∞;1) x=(-3+5)/4=0,5∈(-∞;1) х=-2 - корень уравнения (**)x=-2 -корень х=0,5 корень уравнения(*) уравнения (*) проверим удовлетворяют ли корни условию 1) х|x-1|-2x≥0 2) х|x-1|-2x<0 х=-2 х=2 -2·|-2-1|-2·(-2)=-6+4≥0- неверно 2·|2-1|-2·2=2-4<0- вернох=0,5 х=-2 0,5·|0,5-1|-2·0,5=0,25-1≥0 неверно -2·|-2-1|-2·(-2)=-6+4=-2<0- верноОтвет х=2; х=-2